Functional foods a case study of modified eggs - Leigh, Richard; Video Education Australasia (Australia : Video Education Australasia, 2000)
This video tells the story of the NewStart egg, developed by Professor Farrell of the University of New England. As the story unfolds, the following issues are examined: The'Cholesterol conspiracy'; benefits of Omega-3 fats ; broad concerns about functional foods; marketing complications
Editor, Sasha Trikojus
Keywords: Eggs; Nutrition; Functional foods